Rational design of reduced graphene oxide/TiO2/gold nanorod nanocomposite for complete degradation of polystyrene microplastics in wastewater - UshaVipinachandran, Varsha; Naveenkumar, K.; Haroon, Kabir Hussain Badagoppam; Ashokan, Indhumathi; Sinha, Arup; Maity, Pradip; Bhunia, Susanta Kumar (Advanced Sustainable Systems, 2025)
Our planet is being devoured by plastic consumption every day. Water, soil, and air are deliberately polluted by the ingredients of these nondegradable plastics. Extensive usage of plastic has serious consequences in the environment, wildlife, and human health. A comprehensive approach to eradicate plastics from the planet is therefore imperative. Herein, a ternary nanocomposite subsumed of reduced graphene oxide (rGO), titanium dioxide (TiO2), and gold nanorods (AuNRs) is synthesized and effectively deployed to remove plastics from water as well as degradation of polymer film by both chemically and photocatalytically. The hydrothermally prepared nanocomposite completely removes polystyrene molecules from water, and 1.2 mg of plastic degradation is observed during the photolysis. Conversely, chemical degradation pathway induces the weight loss of 10.7 mg. Both Plasmon-induced interfacial charge transfer transition (PICTT) and Plasmon-induced hot electron transfer (PHET) assist the formation of reactive oxygen species (ROS) that collectively degrades the polymer strands. The spectrochemical and microscopic studies validate the degradation studies with cautious conclusions.
Keywords: chemical degradation; Photocatalysis; plasmonic hot electron; polystyrene microplastics; Reduced graphene oxide